2020
DOI: 10.1007/s13165-020-00321-3
|View full text |Cite
|
Sign up to set email alerts
|

Public attitude towards cow-calf separation and other common practices of calf rearing in dairy farming—a review

Abstract: Public demand for food produced in systems with high animal welfare standards is rising. In terms of animal welfare, the dairy industry has a positive reputation in European countries. However, there are many practices in the dairy industry of which the public is unaware, e.g., zero-grazing, tethering, dehorning, disposal of male calves, and early cow-calf separation. We focused on the latter and reviewed studies addressing public opinions about dealing with calves in dairy farming. We show that most responden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 45 publications
0
34
0
2
Order By: Relevance
“…For each of the four scenarios presented, participants showed the most support for the naturalistic alternative. Previous studies have shown that participants support providing a more natural living environment for animals [ 3 , 34 ], and for practices perceived as being more natural [ 20 , 35 ]. Schuppli et al [ 23 ] found that 80% of participants agreed with allowing pasture access for cows.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For each of the four scenarios presented, participants showed the most support for the naturalistic alternative. Previous studies have shown that participants support providing a more natural living environment for animals [ 3 , 34 ], and for practices perceived as being more natural [ 20 , 35 ]. Schuppli et al [ 23 ] found that 80% of participants agreed with allowing pasture access for cows.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous literature showing public concern towards modern practices [ 3 , 41 , 42 ]. More specifically, previous work has identified opposition to lack of pasture access [ 23 ], disbudding [ 35 ], and cow-calf separation [ 20 ]. We compared attitudes across scenarios and found that participants opposed some practices (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On dairy farms, male cattle are sent to the slaughterhouse at a young age, after being separated from their mothers within hours or days after birth and then often confined for the whole of their brief lives, which do not extend beyond calfhood (Ventura et al 2013;Tuloch & Judge 2018;Placzek et al 2020;Mikuš & Mikuš 2020). Females survive for several years (far less than their normal lifespan) during which they are repeatedly inseminated to gestate and give birth in order to produce enormous quantities of milk from their oversized mammary glands, the result of human manipulation designed to increase production beyond natural limits (Lehenbauer & Oltjen 1998;Dobson et al 2007;Sumner-Thompson et al 2011;Ayadi 2019).…”
Section: Physical Suffering Of Farmed Animalsmentioning
confidence: 99%
“…The common dairy industry practice of permanently separating mother from offspring, at an early age, has attracted increasing concern and criticism [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ] and early permanent separation has been reported as stressful for both mother goats and their kids [ 12 , 13 , 14 , 15 , 16 ]. Maintaining the mother-offspring relationship is likely to have positive consequences for the welfare of the dam and goat kids [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%